Pemberdayaan Kelompok Tani Melalui Pembuatan Pupuk Kompos di Desa Bonto Karaeng Kabupaten Bantaeng: Empowering Farmer Groups Through Making Compost Fertilizer in Bonto Karaeng Village, Bantaeng Regency - Wangsa, Muhammad Arif; Indriani, Indriani; Nursani, Nursani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The final production of the livestock industry is animal waste which needs to be managed well and productively. Improper processing will cause waste and environmental pollution. Bonto Karaeng Village produces a lot of livestock waste which is not used effectively and can pollute the surrounding environment. With the increasing use of livestock waste and agricultural waste, there is a lot of agricultural waste other than animal waste that cannot be utilized optimally. The knowledge and skills of the community and farmers in processing animal waste and coconut fiber into useful organic fertilizer can be increased through community service activities. The local village farmer group took part in a community service project that took place in Bonto Karaeng Village on September 30, 2024. The service activities carried out consisted of observation, socialization, the process of making compost fertilizer, and evaluation. The outcomes of the service activities showed that participants experienced increased knowledge and abilities in processing waste into organic fertilizer. They can also independently produce organic fertilizer to meet farmers' needs and have economic value that can increase farmers' income. Apart from that, it can minimize the use of pesticides and maximize the use of organic materials to build a sustainable agricultural system.